2011
DOI: 10.1186/1556-276x-6-501
|View full text |Cite
|
Sign up to set email alerts
|

High degree of polarization of the near-band-edge photoluminescence in ZnO nanowires

Abstract: We investigated the polarization dependence of the near-band-edge photoluminescence in ZnO strain-free nanowires grown by vapor phase technique. The emission is polarized perpendicular to the nanowire axis with a large polarization ratio (as high as 0.84 at 4.2 K and 0.63 at 300 K). The observed polarization ratio is explained in terms of selection rules for excitonic transitions derived from the k·p theory for ZnO. The temperature dependence of the polarization ratio evidences a gradual activation of the XC e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…With the rapid development of nanometer science and technology, ZnO nanoobjects in different fashions have been successfully synthesized or fabricated by various chemical or physical methods. These ZnO nanoobjects, including nanoclusters [7][8][9][10], nanowires [11][12][13][14], nanotubes [15,16], nanorods (NRs) [17][18][19], and nanoflowers [20][21][22], have received intensive and extensive studies due to their unique electric, thermotic, cytalytic, mechanical, magnetic and optical properties originating from surface effect or quantum size effect. Among these properties, the optical properties of ZnO nanowires or NRs have been the focus of many studies because this kind of nanoobjects can be easily synthesized and has potential applications in making optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanometer science and technology, ZnO nanoobjects in different fashions have been successfully synthesized or fabricated by various chemical or physical methods. These ZnO nanoobjects, including nanoclusters [7][8][9][10], nanowires [11][12][13][14], nanotubes [15,16], nanorods (NRs) [17][18][19], and nanoflowers [20][21][22], have received intensive and extensive studies due to their unique electric, thermotic, cytalytic, mechanical, magnetic and optical properties originating from surface effect or quantum size effect. Among these properties, the optical properties of ZnO nanowires or NRs have been the focus of many studies because this kind of nanoobjects can be easily synthesized and has potential applications in making optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The optical properties of the nanowires were first studied by photoluminescence (PL) measurements on a nanowire sample performed with excitation from a frequency-tripled mode locked Ti:Sapphire laser (pulse width 130 fs; repetition rate 80 MHz) at 267 nm. The wurtzite crystalline structure gives rise to three free exciton transitions, X A , X B and X C , of which the X A and X B excitons are polarized perpendicular to the c-axis whereas the X C exciton is strongly polarized parallel to the c-axis, as confirmed by interband momentummatrix calculations [25,26]. The PL spectrum at 10K, shown in Fig.…”
mentioning
confidence: 73%
“…In one of the reports, the authors showed the growth of ZnO nanowires as shown in Figure 10a using Pt as catalyst [49]. The S t (660 °C) was found to be higher as compared to the one used with Au catalyst.…”
Section: Surface Morphology Investigation Of Nanowiresmentioning
confidence: 97%